WhatsApp in English Class: An Application of Blended Learning in Initiating Students' Interaction - Zulkifli Akhmad; Yuwin R Saleh (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
This study investigated 1) The students' perception of group WhatsApp in the teaching and learning process, which is also well-known as blended learning, and; (2) The process of students' interaction in English via WhatsApp. Data were collected from 60 students of the English Education Department; 52 females and eight males; most are between 19 and 20 years old. The researcher deploys a survey, unstructured interview, and unstructured-descriptive observation. The data analysis revealed that most students responded positively to WhatsApp in blended learning, and only a few responded negatively. The level of students' participation in English interaction via WhatsApp is higher than they do face-to-face since they feel more confident in conveying their ideas via WhatsApp, especially to the lecturer.